2017
DOI: 10.1111/jch.13106
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness, sex, and age difference on hypertensive response to supine bicycle exercise

Abstract: Contributors to a hypertensive response to exercise (HTR) according to sex and age have not been fully evaluated. The authors analyzed a database of supine bicycle exercise stress echocardiography findings. HTR was defined as peak systolic blood pressure ≥210 mmHg for men and ≥190 mmHg for women during exercise. A total of 797 patients (306 [38%] women) were analyzed, with a mean age of 64 ± 10 years. Female sex, hypertension; higher left ventricular ejection fraction, effective arterial elastance, and pulse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Even after adjustment for other risk factors, the association remained significant. Differences were found according to sex and age [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even after adjustment for other risk factors, the association remained significant. Differences were found according to sex and age [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue fractures of elastic elements are often considered to be responsible for age-related increases in aortic PWV ( 21 ). The results of a cross-sectional study showed that women had lower systemic vascular compliance and higher systemic vascular resistance than men ( 22 ). A longitudinal study showed that resistance increased in women and decreased in men with age ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al investigated data from 797 patients (38% women, mean age 64 ± 10 years, 75% with a history of hypertension) and showed that the prevalence of HRE was higher in women than in men. Furthermore, patients with HRE presented with pathologic variations in LV mass index, LAVI, E/e', end diastolic elastance and relative wall thickness, which are echocardiographic parameters of diastolic dysfunction and ventricular remodelling and known risk factors for the development of HFpEF [53].…”
Section: K Review Articlementioning
confidence: 99%